The Structure of the Sugar Residue in Glycated Human Serum Albumin and Its Molecular Recognition by Phenylboronate - Rohovec, Jan; Maschmeyer, Thomas; Aime, Silvio; Peters, Joop A. (Chemistry : a European journal, 2003)
Quantification of the extent of glycation of human serum albumin (HSA) and of haemoglobin provides a record of average mid‐ and long‐term blood‐sugar concentrations, respectively; this is very useful for the management of diabetes. The reaction of D‐glucose with propylamine affords the corresponding Schiff base, N‐propylamino‐D‐glucoside, in the cyclic form. This compound is not stable: upon standing or treatment with acid it is converted, by an Amadori rearrangement, into N‐propylfructosamine. Both amino sugars occur predominantly in the β‐pyranose form. Phenylboronate forms highly stable boronate esters through binding of the cis 1,2‐diol moiety in the furanose form of N‐propylfructosamine. Between pH 5 and 10, an electrostatic interaction between the protonated amino group and the negatively charged boronate moiety affords an additional stabilisation of the ester. The Schiff base, however, has no observable interaction with phenylboronate. In aqueous solution the Schiff base is in equilibrium with propylamine and glucose. Upon addition of phenylboronate, this equilibrium shifts to the side of glucose due to the formation of highly stable phenylboronate esters of the β‐furanose form of this compound. After Amadori rearrangement, the sugar moieties in glycated human serum albumin have a similar structure, they occur as an equilibrium of the β‐pyranose (59 %), α‐furanose (19 %) and β‐furanose (24 %) anomers. The open form was not observed. The β‐furanose anomer is selectively recognised by phenylboronate. A measure of mid‐term blood‐sugar concentrations, useful for the management of diabetes, can be derived from quantification of the extent of glycation of human serum albumin (HSA). After Amadori rearrangement, the sugar moieties in glycated HSA occur as an equilibrium of the β‐pyranose (59 %), α‐furanose (19 %) and β‐furanose (24 %) anomers. The open form is not observed. The β‐furanose anomer is selectively recognised by phenylboronate, as shown.